Pemberdayaan Kader dalam Rangka Pengelolaan Limbah Plastik di Desa Kaliukan Kecamatan Astambul Kabupaten Banjar - Laily Khairiyati; Fujiati Fujiati; Siti Juliati; Emmi Erliyanti; Gabrielle Nida Tarlianty; Karina Nurfatma Apriani; Muhammad Wahyu Ridhani (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2022)
Kaliukan Village, Astambul District, Banjar Regency, is one of the villages where the majority of the people work as farmers. Their income, mainly from agricultural labor, has limitations, especially in conditions during pre-planting and before harvesting. On the other hand, Kaliukan village is a flood-prone area. Reports of people affected by the flood explained that the river's flow became slow due to the accumulation of garbage at the mouth of the river. Plastic waste that accumulates in the living environment and rivers is a problem faced by the people of Kaliukan Village because efforts to reduce the volume of plastic waste have not been managed by the community properly. This community service activity can be a solution by managing bottle and cup waste from mineral water packaging into plastic shreds through the empowerment of RT 1, 2, 3, and 4 Cadres in Kaliukan Village. This program was implemented in May–September 2021 in counseling, training, mentoring and monitoring, and evaluation activities. The results of this activity were a significant increase in knowledge (p-value = 0.020) towards the target of the activity, the formation of waste care cadres, and the implementation of workshops aimed at increasing the skills of cadres and handing over assistance for plastic waste counting equipment. At the monitoring and evaluation, village officials and cadres' commitment was formed to establish the "Amanah Bersama" waste bank. It is hoped that this activity will help preserve environmental cleanliness and make a joint effort to improve the community's economy in Kaliukan Village.